UTR-2 LOW FREQUENCY CONTINUUM SURVEY OF THE NORTHHEN SKY. PART II - Vasilenko, N. M.; Sidorchuk, M. A. (Одеські астрономічні публікації, 2019)
The Ukrainian T-shape radio tele- scope (UTR-2) has been used to carry out a multifre- quency radio survey of a part of the northern sky with coordinates of the declinations +10 ◦ < Dec. < +29 ◦ , and right assertions 0 h < R.A. < 24 h . The observa- tions were performed at very low radio frequencies, 12.6, 14.7, 16.7 20 and 25 MHz. They were fulfilled by scanning the sky due the Earth’s rotation with the five-beam pattern antenna at 11 fixed declinations. The observations for six five-beam strips, that covered the declinations ranges from +10 ◦ to +19 ◦ , the so-called "a fast scanning mode" was used. In this mode, the antenna positions were switched in the cycle between the three selected strips at fixed declinations every 40 seconds in the observational process. For the remaining strips, both the fast scanning mode and the usual observation mode at one fixed declination were used. Each pattern pencil-beams are spaced apart by 23’ in the meridian. The angular size of the beam is about 1 ◦ at 12.6 MHz 0.5 ◦ at 25 MHz at the zenith. The receivers’ bandwidths are 10 kHz at frequencies from 12.6 to 16.7 MHz and 40 kHz at the two highest frequencies. A calibration of the output power was performed with the aid of the etalon noise generator for the each observation. These data surveyed were obtained during the period from 1997 to 2013 only at nighttime. The total number of observation amounted to more than 700 nights. The statistics for each point of the survey varied from 5 to 40 realizations. The results of these observations are the brightness temperature maps presented here at each mentioned above frequencies of the decameter band. However, it should be noted that there are shown "raw" maps without rhe zero level and striping effect corrections. These maps comprise emission from discrete and extended radio sources, the Galaxy and extragalactic background. The most intense radio emission on the maps is observed from the Galactic Plane and the North Polar Spur (NPS).